PENGUATAN MANAJEMEN PESANTREN BERBASIS KEWIRAUSAHAAN MELALUI PROGRAM PENDAMPINGAN UNTUK MEWUJUDKAN KEMANDIRIAN EKONOMI PESANTREN BOARDING SCHOOL DI KECAMATAN PAMIJAHAN: PENGUATAN MANAJEMEN PESANTREN BERBASIS KEWIRAUSAHAAN MELALUI PROGRAM PENDAMPINGAN UNTUK MEWUJUDKAN KEMANDIRIAN EKONOMI PESANTREN BOARDING SCHOOL DI KECAMATAN PAMIJAHAN - Ima Rahmawati; Titin Rustini (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2026)
This community service program aimed to realize pesantren economic independence through strengthening entrepreneurship-based management at boarding school pesantren in Pamijahan District. The program was motivated by limited business governance capacity, weak business planning, poor financial administration, and low utilization of local economic opportunities. The method employed Participatory Action Research (PAR) through needs mapping, FGD, training, intensive mentoring, program implementation, monitoring, and evaluation. The results showed improved managerial competence, indicated by the formulation of business roadmaps, business organizational structures, SOP, financial recording systems, and digital marketing strategies. In addition, partners initiated business diversification based on local potential and community networks. This program proves that participatory mentoring effectively strengthens pesantren economic institutions. The implication of this activity is the availability of an innovative, adaptive, and sustainable pesantren empowerment model to support the Ministry of Religious Affairs of Indonesia priority program on Pesantren Independence and the improvement of national Islamic education quality.